Toward a global orchid taxonomic network - Pupulin, Franco (2013)
The genesis and early establishment of the Epidendra project are reviewed, retracing the scientific, ethical and political reasons that defined its actual shape and contents. The taxonomic structure of the global orchid network, its systematic framework and nomenclatural implications are discussed. The actual figures of the database are presented, and the lines of its future development are pointed out.